Women’s Political Involvement in Local Community Governance Structures in Bugujju Town, Mukono Municipality, Uganda. - Ayoo Winnie Atimango (Uganda Christian University, 2024)
The study examined women's political involvement local community governance structures in Bugujju town, mukono municipality Uganda. This research was guided by objectives which included: analyzing the factors influencing women political participation in local government structures, establishing the role of local structures and suggesting possible strategies that can enhance more women political involvement in local community strucutres within Bugujju Mukono municipality. The study utilized a cross-sectional methodology, collecting data data from a sample population at a single point in time where quantitative method of data collection was used. The data was collected using interviews as a method of data collection, employing purposive sampling, and random sampling. A sample size of 70 respondents who were women in leadrship positions, female leaders, community members and local government officials. The findings showed that while Bugujju as a community has tried several measures to elevate the low level of women political involvement in local community structures. Provision of resources and financial support to overcome obstacles like funding shortages, capacity building and leadership training a strategy suggessted by the community to navigate politics advocate and addressing social cultural barriers which will foster gender equality and promote inclusive governance. Finally the study recommended the need for establishment of robust monitoring and evaluation frameworks to regularly gauge the effectiveness of initiatives promoting women’s participation, mobilzation of male leaders and stakeholders as champions of gender equality, training initiatives that empower women in Bugujju town with skills and confidence to take on leadership and lastly launching of community-wide education and awareness initiatives to confront and transform harmful social and cultural norms.
Undergraduate research